A self-balancing platform on a mobile car - Bushra Amer Tawfeeq; Maher Yahya Salloom; Ahmed Alkamachi (Institute of Advanced Engineering and Science, 2022)
In the last years, the self-balancing platform has become one of the most common candidates to use in many applications such as flight, biomedical fields, and industry. In this paper, the physical prototype of a proposed self-balancing platform that described the self-balancing attitude in the (X-axis, Y-axis, or biaxial) under the influence of road disturbance has been introduced. In the physical prototype, the inertial measurement unit (IMU) sensor will sense the disturbance in (X-axis, Y-axis, and biaxial). With the determined error, the corresponding electronic circuit, DC servo motors, and the Arduino software, the platform overcame the tilt angle(disturbance). Optimization of the proportional-integral-derivative (PID) controllers’ coefficients by the genetic algorithm method effectively affected the performance of the platform, as the platform system is stable and the platform was able to compensate for the tilt angle in (X-axis, Y-axis, and both axes) and overcome the error in a time that does not exceed four seconds. Therefore, a proposed self-balancing platform’s physical prototype has a high balancing accuracy and meets operational requirements despite the platform’s simple design.